Succination of Protein Thiols in Human Brain Aging - Jové, Mariona; Pradas, Irene; Mota-Martorell, Natalia; Cabré, Rosanna; Ayala, Victoria; Ferrer, Isidre; Pamplona, Reinald (Frontiers in Aging Neuroscience, 2020)
Human brain evolution toward complexity has been achieved with increasing energy supply as the main adaptation in brain metabolism. Energy metabolism, like other biochemical reactions in aerobic cells, is under enzymatic control and strictly regulated. Nevertheless, physiologically uncontrolled and deleterious reactions take place. It has been proposed that these reactions constitute the basic molecular mechanisms that underlie the maintenance or loss-of-function of neurons and, by extension, cerebral functions during brain aging. In this review, we focus attention on the role of the nonenzymatic and irreversible adduction of fumarate to the protein thiols, which leads to the formation of S-(2-succino)cysteine (2SC) (protein succination) in human brain. In particular, we first offer a brief approach to the succination reaction, features related to the specificity of protein succination, methods for their detection and quantification, the bases for considering 2SC as a biomarker of mitochondrial stress, the succinated proteome, the cross-regional differences in 2SC content, and changes during brain aging, as well as the potential regulatory significance of fumarate and 2SC. We propose that 2SC defines cross-regional differences of metabolic mitochondrial stress in human brain and that mitochondrial stress is sustained throughout the healthy adult lifespan in order to preserve neuronal function and survival.